The rhetorical structure of newspaper reports: A synergy between corpus, genre and discourse analysis - Hafizah Hajimia; Nur Rasyidah Mohd Nordin; Manvender Kaur Sarjit Singh; Philip Golingai (Universitas Pendidikan Indonesia, 2022)
The pandemic has intensified issues faced by the journalism community in Malaysia. This study is an attempt to help the media industries upskill themselves in terms of the written discourse. This study describes the rhetorical structures in Malaysian newspaper reports, namely The Star, in terms of the rhetorical moves and steps by using the genre theory, corpus-based discourse analysis and corpus analysis. MyCORONAS (Malaysian Corpus of Online Newspaper Articles) corpus of 90 selected news reports consisting of crime news (TSC), environmental news (TSE) and political news (TSP) was compiled and analysed quantitatively and qualitatively to identify the frequency, functions, and patterns of rhetorical moves. The findings identified a nine-move structure for the newspaper reports. The nine-move structure consists of five optional moves and four obligatory moves. Variations in the use of the steps were observed within the sub-genres. Additionally, based on the functions of the moves, it was found that the newspaper report is a hybrid genre with various communicative functions. Based on the patterns of move distribution, the dispersion value shows that the moves are tightly clustered. To conclude, the findings of this study will heighten the awareness of ESP learners on the importance of using appropriate rhetorical moves to write a newspaper report which will help the journalism industries reform themselves during the pandemic.